2022
DOI: 10.1136/bmjopen-2021-050949
|View full text |Cite
|
Sign up to set email alerts
|

Influence of information provided prior to switching from Humira to biosimilar adalimumab on UK patients’ satisfaction: a cross-sectional survey by patient organisations

Abstract: ObjectivesTo investigate the perceptions and experiences of people with specific immune-mediated inflammatory diseases during the process of switching from Humira to biosimilar adalimumab.DesignCross-sectional survey.SettingAn anonymised, self-administered, web-based survey.ParticipantsThe participants were drawn from members and non-members of either the National Rheumatoid Arthritis Society, the National Axial Spondyloarthritis Society, Crohn’s and Colitis UK, or Psoriasis Association. Birdshot Uveitis Socie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Switching treatment and nocebo response to biosimilar therapy may negatively impact medication adherence and lead to poorer clinical outcomes [ 12 , 32 ]. Mitigating the nocebo effect requires increased awareness among prescribers and patients of the strict regulatory evaluation, similar safety and efficacy of biosimilars to their reference product [ 12 ], and enhanced prescriber–patient communications [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Switching treatment and nocebo response to biosimilar therapy may negatively impact medication adherence and lead to poorer clinical outcomes [ 12 , 32 ]. Mitigating the nocebo effect requires increased awareness among prescribers and patients of the strict regulatory evaluation, similar safety and efficacy of biosimilars to their reference product [ 12 ], and enhanced prescriber–patient communications [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some unsuccessful switches have been attributed to patients’ perceptions (the “nocebo” effect [ 16 ]), and reduced efficacy and safety [ 14 ]. Furthermore, the manner and content of communications to patients about the reasons for non-medical switching may greatly influence the outcome [ 17 ]. The lower biosimilar retention rates in open-label switch studies compared to double-blind switch trials suggests that the nocebo effect might also play a role in biosimilar retention rates [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, patients have reported suboptimal communication during a biosimilar transition, including wanting more notice, not being satisfied with the verbal or written information, or not having their concerns satisfactorily dealt with (5, 12). Our participants reported receiving enough notice before the transition occurred, but some also experienced a lack of information and resources.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few studies have explored patients’ experiences with the transitioning process, when considering how frequently patients are transitioned to biosimilars. A recent study surveyed 899 patients in the United Kingdom with immune‐mediated inflammatory diseases (e.g., arthritis, skin psoriasis and Crohn's disease) on shared decision‐making and the information they received during the transition to an adalimumab biosimilar ( 5 ). The survey demonstrated that transitioning was often done with suboptimal communication.…”
Section: Introductionmentioning
confidence: 99%
“…Educating pharmacists is important as some patients transitioning to Amgevita in the United Kingdom reported dissatisfaction with the information, and this was associated with more side effects, difficulty in using the new device, and negative perceptions about symptom control. 39 The results also pose an important question of where the responsibility falls to ensure pharmacists are sufficiently informed. A coordinated approach to sharing information is essential before a medicine brand changes to ensure pharmacists and other healthcare providers obtain up-to-date and balanced information on newly funded pharmaceuticals.…”
Section: Discussionmentioning
confidence: 99%